Letters to Colleagues: A community of practice for navigating and reshaping identity. Issue 1 (1st March 2019) - Nordlund, Carrie
This article discusses outcomes from a study of Letters to Colleagues, a visual and verbal letter-based method of dialogic exchanges as means for spurring deep reflection and professionalism in preservice art educators. Reflective practice heightens educators' learning or consciousness of identity – 'who they are and who they might become as educators'. This article shares Letters to Colleagues, narratives within a community of practice employed in a university teacher preparation programme with aims to further preservice art educators as reflective practitioners. In the processes of Letters to Colleagues preservice art educators regularly tracked aha moments and wonderings from fieldwork that in turn encouraged visual (e.g. drawings, paintings, digital media, etc.) and verbal conversations and reflections with self and others about their multiple identities, personal philosophies, pedagogical dilemmas and decisions, and when necessary resolved internal and external conflicts. Letters to Colleagues utilizes reciprocity and accountability among peer colleagues' letter writing and meaning making where the social whole and the individual constitute each other. The findings support Letters to Colleagues as ongoing reshaping of art educators' adjustable identities. In the process a social discipline emerges within the community of practitioners transforming meanings back and forth from intersubjectivity and intrasubjectivity.